Conversations that matter: using videos to model quality ACP conversations between clinicians and patients. Issue 2 (1st June 2012) - Vig, C; Berg, B; Simon, J
Abstract : In 2008, the "Advance Care Planning: Goals of Care Designation (ACP/GCD) (Adult)" policy was systematically implemented across all sectors within Alberta Health Services, Calgary Zone. A critical component for successful implementation of the policy was clinician development of skills with engaging in quality advance care planning (ACP) conversations. Pre and post policy evaluation has consistently identified ongoing barriers with initiating and engaging in the quality conversations required for successful outcomes with policy adoption. Key challenges reported by clinicians are lack of confidence and competency with approaching patients for the purpose of engaging in ACP conversations. Clinicians frequently identify similar themes found in ACP literature; fear of diminishing hope, lack of skills in initiating and sustaining conversations and fear of causing harm to patients in this process. This presentation will present a series of clinician education videos modelling key components of ACP conversations. The videos provide clinicians with a 'tool box' of phrases and questions they might consider saying in different situations or at different stages of the process of conversations, and provide clear examples of communication techniques such as clarifying, maintaining eye contact and open body language. These videos can be used as a basis for role modelling-based education for all clinicians to practice and improve communicating about advance care planning. Additionally, utilising videos as a teaching methodology can assist with timely and flexible education reducing some of the barriers with accessing skill development and training.